Online shopping behavior on Generation Y in Indonesia - Iffahsari Musyifah; Megawati Simanjuntak (Global Business & Finance Review (GBFR), 2016)
Online shopping behavior is the most preferred shopping method for modern society, especially Generation Y who are always connected to the internet and technology in every aspect of life. Young consumers prefer online shopping because of its convenience, lower price, many choices, time saving, and ease of access anywhere and anytime. This topic was addressed to analyze determinant factors of online shopping behavior on Generation Y's consumers. This research involved 100 undergraduate students of Bogor Agricultural University selected using snowball technique. This research used cross-sectional studys design. Data were collected by self-report using questionnaires and analyzed by using multiple regression analysis. The result showed that monthly allowance and attitudes influenced significantly and positively on online shopping behavior.
Keywords: 650; Attitude; Generation Y; Internet Usage; Lifestyle; Online Shopping